2020
DOI: 10.1186/s13019-020-01336-3
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation or surgical therapy in moderate-severe tricuspid regurgitation caused by long-standing persistent atrial fibrillation. Propensity score analysis

Abstract: Background This study aimed to describe the mid-term outcomes of different treatments in patients with atrial fibrillation caused tricuspid regurgitation. Methods A retrospective study of patients diagnosed as atrial fibrillation caused moderate-severe tricuspid regurgitation undergoing ablation (n = 411) were reviewed. The surgical cohort (n = 114) underwent surgical ablation and tricuspid valve repair; the catheter cohort (n = 279) was selected from those patients who had catheter ablation. Results The e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…dyspnoea) are associated with adverse outcomes after TR surgery 13–15 . Additionally, AF‐associated TR resulted in reduced leaflet coaptation, which increases the recurrence risk of both AF and TR 16,17 . This study showed that higher mortality was associated with older age and refractory AF.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…dyspnoea) are associated with adverse outcomes after TR surgery 13–15 . Additionally, AF‐associated TR resulted in reduced leaflet coaptation, which increases the recurrence risk of both AF and TR 16,17 . This study showed that higher mortality was associated with older age and refractory AF.…”
Section: Discussionmentioning
confidence: 70%
“…[13][14][15] Additionally, AF-associated TR resulted in reduced leaflet coaptation, which increases the recurrence risk of both AF and TR. 16,17 This study showed that higher mortality was associated with older age and refractory AF. Nevertheless, only 45% of all study participants underwent the Maze procedure.…”
Section: Discussionmentioning
confidence: 84%
“…Small studies have also demonstrated that betablockers including carvedilol and bisoprolol improve RV systolic function (49). Some evidence supports the benefit of sinus rhythm restoration on the reduction of TR severity (50,51). However, these studies have been performed in patients with concomitant MR and preserved ejection fraction, and whether the improvement is due to a direct impact on TR per se or to an improvement in MR and left heart characteristics is unknown.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Tethering height was the only risk factor for recurrent AF. 28 In our study the risk factors for AF is clearly identified as all patients having Rheumatic Heart Disease (RHD) 90 out of 90 (100%), Chronic Obstructive Pulmonary Disorder (COPD) 60 out of 60 (100%), Thyroid Disorder 50 out of 50 (100%), Coronary Heart Disease (CHD) 20 out of 20 (100%), Lower Respiratory Tract Infection (LRTI) 20 out of 20 (100%), Lone Atrial Fibrillation (LAF) 10 out of 10 (100%) have affected from AF, whereas the incidence of AF is reported having History of Congestive Heart Failure (CHF) was 28 out 80 (35%).…”
Section: Figure1: Bar Chart Of Atrial Fibrillation Causesmentioning
confidence: 99%